EXAMINING SCHOOL PSYCHOLOGISTS' PERSPECTIVES ABOUT SPECIFIC LEARNING DISABILITIES: IMPLICATIONS FOR PRACTICE. Issue 3 (March 2017) - Cottrell, Joseph M.; Barrett, Courtenay A.
Abstract : Debate regarding the causes of specific learning disabilities (SLDs), precise definitions of SLDs, and the most effective identification methods has persisted for over 50 years. Two prominent schools of thought regarding SLDs exist: (1) biological perspectives and (2) environmental perspectives. Three identification methods are outlined in the Individuals with Disabilities in Education Act of 2004 (IDEA, 2004) and align themselves to the different perspectives: (1) the IQ‐Achievement discrepancy method, (2) the response‐to‐intervention method, and (3) alternative research based procedures (e.g., evaluation of a student's pattern of strengths and weaknesses; PSW). This study used survey methodology ( N = 471) and found that school psychologists' perspectives about SLDs were significantly correlated with preferred identification methods. Preferred identification methods impacted practice even after controlling for individual‐ and school‐level variables. Implications and suggestions for future research are discussed.